Alternatif Penyelesaian Sengketa Larangan Ekspor Nikel Indonesia Di WTO - Prabowo, Hilmi (PROGRESIF: Jurnal Hukum, 2024)
Indonesia has been sued by the European Union for the nickel ore ban form 1 January 2020. That Export Prohibition has done because Indonesia want to downsteraming the nickel by not exporting nickel ore as raw material, but as electrical car battery. European Union feel being aggrieved by that policy. Indonesia has been defeated in the Panel investigation process and appealing to the WTO Appellate Body. WTO is a world trade organization that is actually created to smooth the interests of developed countries, but developing countries WTO members also make various efforts so that the WTO system also provides justice for developing countries so that there is a tug-of-war between developed and developing countries in the WTO. Indonesia's case against the European Union in the nickel export ban dispute is an example of a conflict of interest between developed countries and developing countries within the WTO. WTO rules decides if the Appeal result has been reported mean the result should be obeyed, that mean if Indonesia lose Appeal Indonesia should export nickel ore as raw material again. There is still a chance for Indonesia to win this dispute, but to avoid defeat in order to avoiding defeat Indonesia can choose ways in the WTO Dispute Settlement System. Those ways are Mutually Agreed Solutions, Good Offices, Conciliation, Mediation, and Arbitratio in Pursuant to the Article 25.1 of the DSU.